Intelligent leadership - Mant, Alistair (St Leonards, N.S.W : Allen and Unwin, 1999)
Intelligent leadership. A gallery of intelligent leaders. Nurturing intelligent leadership.
Keywords: Management; Leadership; Organizational change; Leadership; Leadership -- Case studies